2006
DOI: 10.3138/jvme.33.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Communication Education in Veterinary Education in the United Kingdom and Ireland: The NUVACS Project Coupled to Progressive Individual School Endeavors

Abstract: This article reports on the coordination of communications skills training in veterinary schools in the United Kingdom and Ireland and describes the progress and status of training that is occurring in six of these schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 5 publications
0
25
0
2
Order By: Relevance
“…In response to this, most veterinary schools now teach communication skills to undergraduates (Gray et al . , Radford et al . , Mossop & Gray ), commonly in the form of the Calgary‐Cambridge model (Silverman & Kurtz , Adams & Kurtz , Kurtz ).…”
Section: Introductionmentioning
confidence: 99%
“…In response to this, most veterinary schools now teach communication skills to undergraduates (Gray et al . , Radford et al . , Mossop & Gray ), commonly in the form of the Calgary‐Cambridge model (Silverman & Kurtz , Adams & Kurtz , Kurtz ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey of the teaching of end-of-life issues in UK veterinary courses suggested that on average about 21 hours are spent on the topic, distributed randomly among the curriculum (Dickinson and Paul 2014). The National Unit for the Advancement of Veterinary Communication Skills found that students formally trained in communication performed significantly better with clients, suggesting that this can be a learned skill and that further training can be of benefit to veterinary graduates (Gray and Blaxter 2006). …”
Section: Staff Considerationsmentioning
confidence: 99%
“…Numerous papers have described the need for similar communication training for veterinary students. 1416 While several veterinary schools have adapted curricula from medical colleges and now provide clinical communication training to veterinary students, 17,18 it is not universal, which leaves both new graduates and many practicing veterinarians without this training or an awareness of its importance to their practice.…”
Section: Introductionmentioning
confidence: 99%